齿轮变位及修形对齿面接触温度的影响研究 - 于东洋; 张超; 叶盛鉴; 李威; 付文斌; 于方弟 (Jixie chuandong)
The calculation method of tooth surface temperature is studied,based on the model of thermal shock and Hertz contact theory,the calculation formula of instantaneous contact temperature on tooth surface is derived,the calculation problem of gear body temperature and the flash temperature are discussed,the influence of gear shift coefficient and modification parameters on transient contact temperature of gear tooth is analyzed,the change rule of the flash temperature along the meshing line is revealed,the research results show that the proper choice of gear shift coefficient and modification parameters can significantly improve the resistance scuffing performance of gear transmission system,avoid scuffing failure.